IMPROVING STUDENTS’ SPEAKING SKILL THROUGH CONVERSATION - Hijril Ismail (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2014)
The study are to find out the implementation of conversation in teaching speaking to English students  at fifth semester of Muhammadiyah University of Mataram 2013and to know the students’ responses to the use of conversation in teaching and learning process. Thisresearch is an action research. In this study the researcher uses action research theory proposed by Kemmis and McTaggart. The participants of the research are English students at fifth semester of Muhammadiyah University of Mataram. The research instrument used by the writer is in the form of observation checklist, test, and questioners. The data in the researchare mainly gathered through the use of observation, tests, andquestionnaires. After the data are collected, the researcher analyzes them. The finding of the research shows that the implementation of conversation can improve English students’ speaking skill at fifth semester of Muhammadiyah University of Mataram 2013.The main score of cycle one is 5.7. And the main score of cycle two is 7.0. The students’ responses were positive when conversations were applied in teaching speaking.